The Consumption Discount Rate for the Distant Future (if we do not die out) - Koen Vermeylen (Tinbergen Institute, 2013)
Gollier and Weitzman (2010) show that if future consumption discount rates are uncertain and persistent, the consumption discount rate should decline to its lowest possible value for events in the most distant future. In this paper, I argue that the lowest possible growth rate of consumption per capita in the distant future is zero (assuming that humans do not die out). Substituting in the Ramsey rule shows then that the lowest possible consumption discount rate for the distant future is equal to the lowest possible utility discount rate of the population (according to the descriptive approach to parameterizing the Ramsey rule) or to the utility discount rate of the social evaluator (according to the prescriptive approach). In both cases, there are strong reasons to set the consumption discount rate for the distant future at a value which is virtually zero.
Keywords: O4; Q5; 330; discount rate; climate change; cost-benefit analysis; prescriptive; descriptive